The first cryptic genus of Ixodida, Cryptocroton n. gen. for Amblyomma papuanum Hirst, 1914: a tick of North Queensland, Australia, and Papua New Guinea - Barker, Stephen C.; Kelava, Samuel; Mans, Ben J.; Apanaskevich, Dmitry A.; Seeman, Owen D.; Gofton, Alexander; Shao, Renfu; Teo, Ernest J. M.; Evasco, Kimberley L.; Soennichsen, Kari F.; Barker, Dayana; Nakao, Ryo (Zootaxa, 2024)
We describe a new genus Cryptocroton n. gen. for Amblyomma papuanum Hirst, 1914, a tick of North Queensland, Australia, and Papua New Guinea.